Design Automatic Drip Irrigation Integrated of Solar Energy Soil Moisture Based as a Efforts To Optimize The Use of Water - THABED THOLIB BALADRAF (Gontor AGROTECH Science Journal, 2020)
Abstract: Agriculture plays a role in providing foods, feeds and energies. Irrigation is an important factor that has a direct impact on crop quality and quantity. Indonesia has 70% dry land which produces food commodities, namely corn, soybeans, cassava and sweet potato. Solar energy based soilmosture integrated automatic drip irrigation has excellent long terms prospects for sustainable agriculture. This study aims to determine the design of solar energy-based integrated solar drip irrigation system, to determine the potential of solar powered drip irrigation, and to determine agricultural innovations that play a role in handling water availability problems. Researchers create irrigation by utilizing renewable energy that it is environmentally friendly. Researchers made a design and carried out three tests, namely testing of soil moisture standards to test automation of tools, testing of solar panels to determine power, and testing the comparison of automatic drip irrigation integrated solar energy based on soilmosture with manual irrigation. The test results show that the tool works automatically when the humidity of the soil is less than 30%, the integrated solar energy drip irrigation will work, the solar panel test produces 0.6 kWh of maximum power which means it is sufficient and the comparison test of automatic drip irrigation is integrated with solar energy based on soilmosture. Manual irrigation, it shows that the sun energy-based integrated solar drip irrigation is 55% more effective than manual irrigation.